Impact of influent deviations on polymer coagulant dose in warm lime softening of synthetic SAGD produced water. (15th July 2021) - Zhang, Lu; Mishra, Dinesh; Zhang, Kailun; Perdicakis, Basil; Pernitsky, David; Lu, Qingye
Highlights: Coagulant dose increased linearly with increasing concentration of HA and silica. Coagulant dose increased slightly with increasing concentration of lime and soda ash. Coagulant dose remained almost unchanged with increasing concentration of hardness. Coagulant dose remained almost unchanged with increasing concentration of clay. Coagulant dose remained almost unchanged with increasing concentration of MgO. Abstract: Warm lime softening is commonly used to reduce hardness, silica, and a small fraction of organic matter from steam-assisted gravity drainage (SAGD) produced water through the addition of lime, soda ash, MgO, coagulant and flocculant. We report a systematic study on the impact of solution chemistry on the epichlorohydrin-dimethylamine coagulant demand for the treatment of synthetic SAGD produced water. Concentrations of magnesium, calcium, sodium bicarbonate, clay (mimicking suspended solids), sodium metasilicate (representing silica), and humic acid (mimicking dissolved organic matter) were varied to study their impact on coagulant demand. The impact of the concentration of lime, soda ash, and MgO on coagulant demand was also studied. Within the studied concentration range, the coagulant dose increased linearly with increasing concentration of humic acid (Ycoagulant = 29 + 0.703XHA ) and silica (Ycoagulant = 52 + 0.537Xsilica ), and increased slightly with increasing concentration of lime and soda ash, but remained almost unchanged with increasing concentration of dissolved hardness, clay, or MgO. The observations were correlated to the understanding of the electrokinetic properties of CaCO3 and Mg(OH)2 particles in lime softening. The findings provide insights for evaluating onsite coagulant dose and optimizing the process. Graphical abstract: Image, graphical abstract